Exporters’ use of emotional intelligence to sustain quality relationships with foreign customers - Leonidou, Leonidas C.; Aykol, Bilge; Larimo, Jorma; Kyrgidou, Lida P.; Christodoulides, Paul (My University, 2019)
Anchored on Emotion Regulation Theory (ERT), this study builds a model that conceptualizes the associations among emotional intelligence, relationship quality, and long-term orientation in Exporter-Importer business relationships. Using survey data collected from 262 Greek export manufacturers, it was found that there is a positive impact of an exporter’s level emotional intelligence on the quality (i.e., satisfaction, trust, cooperation, and commitment) of its relationship with the importer buyer. These positive effects are stronger when foreign buyers are based in countries characterized by high levels of uncertainty avoidance, but weaker in the case of importers coming from cultures characterized by high levels of power distance, individualism, and masculinity. Importantly, high levels of Exporter-Importer (E-I) relationship quality subsequently improve the long-term orientation in the relationship. Various theoretical and managerial implications are extracted from the study findings, as well as directions for future research.
Keywords: Anchored on Emotion Regulation Theory (ERT)